2017
DOI: 10.1007/s12250-017-4049-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Kaposi’s sarcoma-associated herpesvirus in Uygur and Han populations from the Urumqi and Kashgar regions of Xinjiang, China

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is the infectious etiologic agent associated with Kaposi's sarcoma (KS), primary effusion lymphoma, and multicentric Castleman disease. It has been shown that high KSHV prevalence and high incidence of both classic KS and AIDSassociated KS are found mostly among people of Uygur ethnicity in Xinjiang, while people of Han ethnicity in Xinjiang have a higher KSHV seroprevalence than those of other Han populations in mainland China. However, it is still unclear why th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Previous studies, including ours, have demonstrated that KSHV is highly prevalent in Xinjiang, China, but most of them were restricted to high‐risk groups . However, epidemiological study investigated the current status of KSHV infection and potential correlates in general population was relatively scarce .…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Previous studies, including ours, have demonstrated that KSHV is highly prevalent in Xinjiang, China, but most of them were restricted to high‐risk groups . However, epidemiological study investigated the current status of KSHV infection and potential correlates in general population was relatively scarce .…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies, including ours, have demonstrated that KSHV is highly prevalent in Xinjiang, China, but most of them were restricted to high-risk groups. 17,22,23 However, epidemiological study investigated the current status of KSHV infection and potential correlates in general population was relatively scarce. 16,18 The current study can play as an important supplement to the scarcity of KSHV data in China and can help to unveil the epidemiological characteristics of the certain virus in this country.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zeng and colleagues report an investigation on the KSHV prevalence in Uygur and Han populations from the Urumqi and Kashgar regions of Xinjiang, China. They find the potential correlation between KSHV prevalence and different ethnicities in endemic areas of Xinjiang, and several environmental factors including population migration may affect KSHV infection rates or KS incidence (Zheng et al, 2017). Meanwhile, Zhang and colleagues report a comprehensive meta-analysis on the epidemiological features of KSHV among intravenous drug users (IDUs) worldwide, and find IDUs are at higher risk of the KSHV infection globally, when compared with the general population, regardless of geographical region or HIV-infection status (Fang et al, 2017).…”
mentioning
confidence: 99%